A diamond NV centers‐based magnetic field sensor using a high‐Q waveguide bandpass filter. Issue 12 (26th October 2022) - Ma, Weiming; Wang, Zhaokai; Gao, Yang; Li, Lei; Du, Guanxiang; Guo, Haizhong
Abstract: In diamond nitrogen‐vacancy (NV) magnetic field sensors, microwave delivery and irradiation with efficient, uniform, and wide dynamic range are necessary to achieve more accurate measurement and higher sensitivity. Here, we report on the development of a triple‐mode broadband waveguide bandpass filter (BPF), which uses a high‐Q metallic cavity to transfer the microwave and excite the diamond NV spin ensembles. This BPF provides a more efficient, low‐loss, uniform, and broadband microwave signal, as well as a closed space for the NV‐quantum sensor. The developed BPF exhibits a large fractional bandwidth (FBW) of 34.8% with a center frequency of 2.87 GHz, and this leads to improve the measurable static magnetic field range up to 5.36 × 10 −2  T. Experimental results show that the sensitivity is improved to 14.67 μT/Hz 1/2 compared to the patch antenna of 188.49 μT/Hz 1/2, that is usually used in the conventional diamond NV‐based quantum sensors.